Seaweed Diversity and Conservation on the Warambadi Seashore of Sumba Island: Substrata and Seasonal Phenomenon - Anggadiredja, Jana Tjahjana (Jurnal Teknologi Lingkungan, 2017)
The interaction between species and species diversity with their growing habitats are essential in the conservation of species. This study deals with the diversity and conservation of seaweed (marine macro-algae) with the emphasis on substrata habitats (sandy and rocky shores) and seasonal conditions (rainy and dry seasons). The study was carried out on the Warambadi seashore of Sumba Island. The t-test analysis showed that the Ã¢â‚¬Å“species diversity index of algaeÃ¢â‚¬Â (HÃ¢â‚¬â„¢) on both sandy and rocky substrata did not significantly different. The (HÃ¢â‚¬â„¢) during both rainy and dry seasons on different substratum (sandy and rocky substrata) did not show any significant differences. The two-way anova analysis recorded that the (HÃ¢â‚¬â„¢) and the number of algae species were not affected by the differences of both substrata and seasons, but it was significantly affected by the interaction between the types of substratum and season. The study also reported that the types of substrata and seasons affected the (HÃ¢â‚¬â„¢) of Chlorophyceae but not by of their interaction, and the (HÃ¢â‚¬â„¢) of Rhodophyceae was affected by the types of substratum and season but not by their interaction. Moreover, the types of substratum and season affected the (HÃ¢â‚¬â„¢) of Phaeophycea, but their interaction did not affect such diversity index. Substrata and seasonal phenomenon also indicate that the types of substratum, season, and their interactions affected the number of species Chlorophyceae, Rhodophyceae, and Phaeophyceae.Keywords:Ã‚Â  seaweed, diversity, conservation, substrata, season